The Influence of Work Flexibility and Work-Life Balance with Job Training as a Moderating Variable on Job Satisfaction of Consultants in DKI Jakarta - Sofyan, Pahrizal; Elmi, Farida (Indonesian Journal Publisher, 2024)
This study is driven by concerns regarding job satisfaction among accounting and tax consulting professionals in DKI Jakarta who are engaged in remote work. The study focuses on three main factors supporting remote work: work flexibility, work life balance, and job training. This is a quantitative study using inferential methods. The population consists of all employees working as accounting and tax consultants in the DKI Jakarta area. The sampling technique is non-probability with purposive sampling. The sample size determination follows Tabachnick's theory, which suggests taking 5 to 10 times the number of indicators. This study has 41 indicators, and the sample size taken is 210 employees, with data management tools using SmartPLS 4 application. The results of this study indicate that work flexibility, work life balance, and job training have a positive and significant impact on job satisfaction, and job training moderates and strengthens the effect of work flexibility on job satisfaction and the effect of work life balance on job satisfaction. Recommendations for future research include exploring alternative indicators that have the weakest influence on each variable of work flexibility, work life balance, and job training, as well as expanding the research coverage area.